Exercise Therapy to Reduce Anxiety (ExTRA) in mid-life and later-life adults: study protocol - Dr Terence W.H. Chong; Ms Julia McCurry; Mr Andi Partovi; Ms Jenny Southam; Dr Christina Bryant; Dr Kay L. Cox; Ms Alissa Westphal; Dr Eleanor Curran; Samantha Loi; Kaarin J. Anstey; Nicola T. Lautenschlager (Archives of Gerontology and Geriatrics Plus)
Background: Anxiety in mid-life and later-life is highly prevalent and causes significant distress and disability. There is increasing evidence supporting the potential effectiveness of exercise interventions for reducing clinically significant anxiety. Self-directed online interventions can be scalable and thus reach more people. Aims: The Exercise Therapy to Reduce Anxiety (ExTRA) project aims to assess the feasibility and acceptability of an 8-week web-based exercise intervention with the innovation of being self-directed, and facilitated by wearable activity monitors (WAMs) and tailored behaviour change strategies to reduce anxiety in mid-life and later-life adults with clinically significant anxiety. Methods: ExTRA will recruit 20-30 community dwelling adults aged 40-79 years with clinically significant anxiety. The self-directed 8-week web-based exercise intervention includes information and strategies to support participants to meet Australian national physical activity guidelines. The intervention is adapted from previous face-to-face trials and includes strategies to support participants living with anxiety. Feasibility will be measured by screening and retention rates. Acceptability will be measured by website usage data, online outcome measure completion, and an evaluation questionnaire. Other outcome measures include anxiety measured by the Depression Anxiety Stress Scales, and physical activity measured by the Global Physical Activity Questionnaire and a WAM. Results: Findings will demonstrate whether this intervention is feasible and acceptable, and provide preliminary efficacy data. Conclusions: The findings of this pragmatic real-world study will be valuable in guiding development of future trials, including randomised controlled trials of scalable and accessible exercise interventions to reduce the distress, disability and cost of anxiety.